Involvement of CX3CL1/CX3CR1 axis in etanercept therapy for patients with active rheumatoid arthritis - Sato, Michihito (Open Access Rheumatol, 2011)
OBJECTIVE: To examine the relationship between serum chemokine levels and patient responsiveness in rheumatoid arthritis (RA) patients to etanercept (ETN) and the influence of ETN administration on serum chemokine levels. METHODS: Serum levels of the chemokines CX3CL1, CXCL8, CXCL10, and CCL3 were quantified prior to (at baseline) and after 14 weeks of treatment with ETN in 20 patients using enzyme-linked immunosorbent assay. Disease status was assessed using the Disease Activity Score (DAS28). The response to ETN was classified according to the European League Against Rheumatism (EULAR) response criteria. RESULTS: By 14 weeks, ETN produced a significant overall reduction in DAS28 among the 20 patients with RA; eight patients achieved a good response, and 10 patients achieved a moderate response based on EULAR response criteria. A significant reduction in CX3CL1 was observed in the responsive group, although ETN treatment had no significant effect on the serum levels of the other three chemokines. In addition, the messenger ribonucleic acid expression of CX3CR1 in peripheral blood mononuclear cells and the cell-surface expression of CX3CR1 protein in peripheral blood CD8(+)CD3(+) T cells were both decreased after ETN treatment. CONCLUSIONS: Our results suggest that the CX3CL1 and CX3CR1 in patients with active RA may be sensitive to antitumor necrosis factor-α therapy and confirm that CX3CL1/CX3CR1 axis plays a crucial role in the pathogenesis of RA.